Applying Stavenhagen's Analytical Approach to Research on Argentine Agrarian Social Structure. (March 2018) - Chazarreta, Adriana
Rodolfo Stavenhagen's analytical approach, as laid out in his 1965 "Seven Erroneous Theses about Latin America, " prioritized a dialectical perspective and relationships of functionality between two dynamics within a single structure and crystallized in fundamental conceptual proposals such as internal colonialism and a focus on the analysis of agrarian social structure. Application of the approach to current research problems in Argentina sheds light on the changes in agrarian social structure that have taken place in recent decades, in particular changes in dominant forms of land tenure, the relations of production, and the functional relationships between areas at different levels of development. La perspectiva analítica que Rodolfo Stavenhagen desarrolla en "Siete tesis equivocadas sobre América Latina " prioriza la perspectiva dialéctica y las relaciones de funcionalidad entre dos dinámicas de una misma estructura y cristalizada en propuestas como el concepto de "colonialismo interno" y en el análisis de la estructura social agraria. La actualidad de este abordaje para definir algunos problemas de investigación que remiten a los cambios ocurridos en las últimas décadas en la estructura social agraria de Argentina arroja luz sobre cambios a las formas dominantes de propiedad y tenencia de la tierra, a las relaciones de producción en el agro y a las relaciones de funcionalidad que se establecen entre zonas o áreas de diferentes niveles de desarrollo.